Physiological Evaluation of Personal Protective Ensembles Recommended for Use in West Africa. (20th March 2017) - Coca, Aitor; Quinn, Tyler; Kim, Jung-Hyun; Wu, Tianzhou; Powell, Jeff; Roberge, Raymond; Shaffer, Ronald
ABSTRACT: Objective: Personal protective equipment (PPE) provides health care workers with a barrier to prevent human contact with viruses like Ebola and potential transmission of the disease. However, PPE can also introduce an additional physiological burden from potentially increased heat stress. This study evaluated the human physiological and subjective responses to continuous light exercise within environmental conditions similar to those in West Africa while wearing 3 different, commonly used PPE ensembles (E1, E2, and E3). Methods: Six healthy individuals were tested in an environmental chamber (32°C, 92% relative humidity) while walking (3 METs, 2.5 mph, 0% incline) on a treadmill for 60 minutes. All subjects wore medical scrubs and PPE items. E1 also had a face shield and fluid-resistant surgical gown; E2 additionally included goggles, coverall, and separate hood; and E3 also contained a highly impermeable coverall, separate hood, and surgical mask cover over the N95 respirator. Results: Heart rate and core temperature at the end of the exercise were significantly higher for E2 and E3 than for E1. Subjective perceptions of heat and exertion were significantly higher for E2 and E3 than for E1. Conclusions: Heat stress and PPE training, as well as the implementation of a work-to-rest ratio that avoids dehydration and possible heat stress issues, are recommended. ( Disaster Med Public Health Preparedness . 2017;11:580–586)